Optimizing Customer Satisfaction on the Shopee E-Commerce Platform: A Comprehensive Analysis of E-Logistics Mediated by Electronic Service Quality and Feature Utilization - arvianti farah natsya (University of Merdeka Malang, 2024)
This research aims to evaluate the influence of e-logistics, e-service quality, and feature usage on customer satisfaction in the context of Shopee application usage in Indonesia. Through data analysis, the results in Table 2 indicate that hypotheses 1 to 5 are accepted with significant path coefficients. Thus, a strong positive influence is found between the variables e-logistics, e-service quality, feature usage, and customer satisfaction. Furthermore, the results of testing hypotheses 6 and 7 in Table 3 reveal that e-service quality successfully mediates the influence of e-logistics on customer satisfaction effectively, while the hypothesis 7 regarding feature usage as a mediator is not proven to be significant. This research underscores the importance of enhancing electronic service quality (e-service quality) as an effective strategy to improve customer satisfaction in the context of e-commerce, particularly on the Shopee platform.